TATA KELOLA PERUSAHAAN DAN KECURANGAN PELAPORAN KEUANGAN: STUDI KASUS INDUSTRI BARANG KONSUMEN DI BEI - Candra, Rudi; Juliani, Meily; Handayani, Wiwin (Catholic University Musi Charitas, 2024)
This research aims to investigate the impact of corporate governance on financial reporting fraud in the consumer goods industry listed on the Indonesia Stock Exchange (IDX). The corporate governance variables considered include board independence, the presence of a remuneration committee, CEO financial expertise, the presence of a financially literate board, board effort coverage, and managerial ownership. The research sample consists of 69 companies in this industry during the period 2018-2022. The data analysis method used is panel regression. The results of panel regression tests using Eviews 12 and IBM SPSS Statistics 25 show that the presence of a remuneration committee has a significant positive impact on reducing financial reporting fraud. However, the board independence variable does not have a significant effect on financial reporting fraud. Similarly, other variables such as CEO financial expertise, board financial expertise, board effort coverage, and managerial ownership also do not have a significant influence. The implications of these findings are discussed in the context of improving corporate governance practices to mitigate the risk of financial reporting fraud.